2008
DOI: 10.1002/jtr.699
|View full text |Cite
|
Sign up to set email alerts
|

Tourism activity, terrorism and political instability within the commonwealth: the cases of Fiji and Kenya

Abstract: This paper discusses the effects of terrorism and political unrest on the level of tourism activities in two developing countries that are a part of the Commonwealth, Kenya and Fiji. The paper explores the nature of the attacks and their impacts on the case studies in terms of the effects on the number of tourism arrivals and the volume of receipts. The responses of the governments, the media and the international communities are also examined to see if there are any guidelines to the likely magnitude and dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 148 publications
(112 citation statements)
references
References 18 publications
6
104
0
2
Order By: Relevance
“…According to the literature, we argue that more democratic countries exhibit higher political stability (Dutt and Mobarak, 2015), which in turn encourages economic development and tourism activity (Farmaki et al, 2015). Interestingly, there is evidence that extended political unrest, as compared to one-off short-term political incidents, has remarkably more devastating results for tourism (Fletcher and Morakabati, 2008). Thus, it makes sense to assume that long-term political turbulence can severely hit tourism and the economy as a whole.…”
Section: Datamentioning
confidence: 99%
“…According to the literature, we argue that more democratic countries exhibit higher political stability (Dutt and Mobarak, 2015), which in turn encourages economic development and tourism activity (Farmaki et al, 2015). Interestingly, there is evidence that extended political unrest, as compared to one-off short-term political incidents, has remarkably more devastating results for tourism (Fletcher and Morakabati, 2008). Thus, it makes sense to assume that long-term political turbulence can severely hit tourism and the economy as a whole.…”
Section: Datamentioning
confidence: 99%
“…However, political events such as a coup and internal political problems have far more severe impacts on tourism activity than one-off terrorist attack incidents (Fletcher & Morakabati, 2008). Similarly, Neumayer (2004) found that a substantial increase in terrorist events lowers tourist arrivals by 8.8%; however, a substantial increase in human rights violation reduces tourist arrivals by 32%.…”
mentioning
confidence: 99%
“…Ayrıca tamamen dışsal faktör olarak kabul edilen yabancı ülke gelirlerindeki artışın da ülke turizmindeki büyümeye olumlu katkıda bulunduğu gözlenmiştir. Fletcher and Morakabati (2008), "Tourism Activity, Terrorism and Political Instability within the Commonwealth: The Cases of Fiji and Kenya" adlı çalışmasına göre, dünyanın herhangi bir yerine ya da bir destinasyona ziyaret sırasında algılanan veya var olan seyahat riskleri, turistlerin temel ihtiyaçlarından birisi olan kişisel güvenlik algısına etki edeceği için turistlerin vereceği kararlar da bu durumdan etkilenebilir. Bunun sonucunda turistler; alternatif destinasyonlara yönelmekten, seyahatin iptaline varana kadar değişik şekilde tepki gösterebilirler.…”
Section: Li̇teratürunclassified